2015
DOI: 10.1002/hed.24030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and costs of readmissions at an academic head and neck surgery service

Abstract: The 30dURs in patients who undergo head and neck surgery can be low, but costly. Identifying patients at risk for 30dUR will help develop preventative strategies. © 2015 Wiley Periodicals, Inc. Head Neck 38: E502-E510, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
119
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(140 citation statements)
references
References 35 publications
16
119
4
1
Order By: Relevance
“…Hospital re-admission rate is now used as a health care quality indicator though multiple studies have shown that high re-admission rate is not associated with inferior care [915]. The Patient Protection and Affordable Care Act of 2010 identified 30-day unplanned hospital re-admissions as a major contributor to Medicare overspending and this has driven the push to penalize facilities with high re-admission rates [14]. This push for quality-based reimbursement was proposed by the Center for Medicare and Medicaid Services and has directed financial penalties for institutions whose quality outcomes, such as re-admission rates and complications, are below acceptable standards [1517].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hospital re-admission rate is now used as a health care quality indicator though multiple studies have shown that high re-admission rate is not associated with inferior care [915]. The Patient Protection and Affordable Care Act of 2010 identified 30-day unplanned hospital re-admissions as a major contributor to Medicare overspending and this has driven the push to penalize facilities with high re-admission rates [14]. This push for quality-based reimbursement was proposed by the Center for Medicare and Medicaid Services and has directed financial penalties for institutions whose quality outcomes, such as re-admission rates and complications, are below acceptable standards [1517].…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of 30 day hospital re-admissions in head and neck surgery patients is roughly 10% [14,15]. Our study is not the first study to evaluate risk factors for re-admission in head and neck cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations